2019
DOI: 10.2298/gensr1901047m
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavone concentrations in soybeans suitable for growing in Europe

Abstract: Isoflavones are nutraceuticals with many different medical benefits found abundantly in soybean (Glycine max (L.) Merr.) seeds. The prerequisite of utilising this valuable source of bioactive compounds and creating quality stock for the pharmaceutical and functional food industries is the screening of available soybean germplasm for isoflavone content. The objectives of this research were to determine the isoflavone concentrations (total isoflavones, daidzein, genistein, glycitein) in 22 high-yielding soybean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Two of the four target isoflavones investigated were found in all analyzed samples (Figure 3). Daidzein and genistein are considered as the principal isoflavones of soy and soy products [33]. On the other hand, formononetin and biochanin A are of much lower abundance in soy products.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the four target isoflavones investigated were found in all analyzed samples (Figure 3). Daidzein and genistein are considered as the principal isoflavones of soy and soy products [33]. On the other hand, formononetin and biochanin A are of much lower abundance in soy products.…”
Section: Resultsmentioning
confidence: 99%
“…Murphy et al [199] determined 160-370 mg 100 −1 g range for TI content in RIL population tested in 2-year, multilocation trials in Canada, while Adie et al [194] Although breeding of isoflavone content at the Agricultural Institute Osijek is at its beginnings, some shifts in the right direction have been made which can be seen from the higher average isoflavone contents in elite breeding lines than in standard cultivars of the same MG (Table 4). In Matoša Kočar et al [195] study, genistein was the most abundant isoflavone component, followed by daidzein and glycitein. The same order of abundance was determined in the research by Lozovaya et al [198] for two French and three US cultivars, whereas Sumardi et al [215] researched 34 black soybeans in Indonesia and found that daidzein content was higher in 31 genotypes.…”
Section: Isoflavonesmentioning
confidence: 92%
“…The most studied isoflavones are genistein, daidzein and glycitein [191]. As a quantitative trait controlled by many minor genes [192], isoflavone content in soybean seed largely depends on the environment [185,[193][194][195], to the extent that even the smallest changes in the microclimate can cause significant changes in the isoflavone contents. For example, it is reported that lower temperatures during the seed fill period increase the isoflavone content, whereas environments which were warmer and drier resulted in lower isoflavone contents [196][197][198][199].…”
Section: Isoflavonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most studied isoflavones are genistein, daidzein and glycitein [191]. As a quantitative trait controlled by many minor genes [192], isoflavone content in soybean seed largely depends on the environment [185,[193][194][195], to the extent that even the smallest changes in the microclimate can cause significant changes in the isoflavone contents.…”
Section: Isoflavonesmentioning
confidence: 99%